Professional Development and Workplace Learning 2016
DOI: 10.4018/978-1-4666-8632-8.ch062
|View full text |Cite
|
Sign up to set email alerts
|

Twitter Chat as an Informal Learning Tool

Abstract: This case study focuses on Twitter as an informal learning tool. Specifically, the authors examine user-created Twitter chats using one specific chat, #sachat, as a case study. #sachat is a weekly one-hour chat held on Twitter and populated by higher education professionals in the field of student affairs (e.g. college admissions, advising, housing, new student orientation). The authors contrast this chat with other ways in which student affairs and higher education professionals are using Twitter. Using metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…These networked practices fill a larger gap in professional competency development among postsecondary educators. Unlike the student affairs chats (#sachat) that are organized as an informal learning resource (Guidry & Pasquini, 2013), the academic advising (#acadv) chat features specifics about the occupational role and designated responsibilities of academic advising, (Cronin, 2017) and acquire a greater understanding of the academic advising role in higher education. They express interest in openly contributing and sharing knowledge with other academic advising professionals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These networked practices fill a larger gap in professional competency development among postsecondary educators. Unlike the student affairs chats (#sachat) that are organized as an informal learning resource (Guidry & Pasquini, 2013), the academic advising (#acadv) chat features specifics about the occupational role and designated responsibilities of academic advising, (Cronin, 2017) and acquire a greater understanding of the academic advising role in higher education. They express interest in openly contributing and sharing knowledge with other academic advising professionals.…”
Section: Discussionmentioning
confidence: 99%
“…We built upon previous empirical work to examine the way structured Twitter chats provide online professional development within a community. Guidry and Pasquini (2013) shared the #sachat case study of student affairs educators using a hashtag for nonformal learning during weekly moderated chats and nonscheduled chat time to discuss trends, issues, and ideas for campus support services. Ford, Veletsianos, and Resta (2014) investigated an emergent social network, #PhDChat, and found that this organic community offers social and emotional advice, support, and resources for doctoral scholars.…”
Section: Professional Networked Practices On Twittermentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most interesting features of social media in education is its possibility of interaction between users, as various studies prove that these generate IL communities of connected users, with possibilities to remain temporary or permanently in time (Carpenter et al, 2018;Ceron, 2018;Gilbert, 2016;Guidry and Pasquini, 2016).…”
Section: Introductionmentioning
confidence: 99%